In Search of a Strategy for Innovation Policy of Polish Economy - Witold Kasperkiewicz; Edyta Dworak (Comparative Economic Research. Central and Eastern Europe, 2009)
The paper considers the very important problem of innovativeness of Polish economy with particular attention given to its innovation policy. The purpose of the paper is to explain the character of innovation policy which has been implemented in Poland since the beginning of economic transformation. Additionally, the paper attempts to evaluate the level of innovativeness of Polish economy. The analysis is based on the set of indicators applied in the European Innovation Scoreboard and Statistical Survey presenting in Statistical Yearbook of Poland. Developing effective and consistent innovation policy requires choice of a particular strategy of innovation development which forms the basis for the policy. One can distinguish two such models in modern economy. In the first model, scientific and technical achievements of domestic R&D sector constitute the main factor indispensable for development of innovation. Investments in domestic scientific and development research determine invention and innovation supply. This model is applied in innovation policy of well-developed economies (Japan, the USA, Germany and Sweden). In contrast, the second model, referred to as adaptive, is based on import of new technologies. Poland should develop an adaptive model, however, its effectiveness will be dependent on the increase of the level of R&D investments, especially in the case of enterprises. The problem is that creative adaptation of imported technologies requires appropriate investments in financing domestic R&D institutions. The paper is divided into three parts. First deals with the characteristics of innovative potential and innovative activity of Polish economy. Second is devoted to the problem of innovation policy in Poland. Considerations presented in this part allow to come to a few conclusions concerning evaluation of innovation policy implemented in Poland. The last part discusses the issue of innovation strategy suitable for development of Polish economy in long run.
Keywords: 330